Vida Saludable: ¿Que son las medicinas? - Karla P. Shelnutt (EDIS, 2011)
This revised 1-page handout is the Spanish-language version of FCS8855/FY1036: Healthy Living: What Are Medicines? Word Search. It was written by Karla P. Shelnutt and published by the UF Department of Family, Youth and Community Sciences, September 2011.